Skin Mycobiota of the Captive Giant Panda (Ailuropoda melanoleuca) and the Distribution of Opportunistic Dermatomycosis-Associated Fungi in Different Seasons - Ma, Xiaoping; Li, Gen; Jiang, Yaozhang; He, Ming; Wang, Chengdong; Gu, Yu; Ling, Shanshan; Cao, Sanjie; Wen, Yiping; Zhao, Qin; Wu, Rui; Zuo, Zhicai; et al. (Frontiers in Veterinary Science, 2021)
Dermatomycosis is the second major cause of morbidity of giant panda (Ailuropoda melanoleuca), and seriously endangers its health. Previous observations indicated that the occurrence of dermatomycosis in the giant panda varies in different seasons. The skin microbiota is a complex ecosystem, but knowledge on the community structure and the pathogenic potentials of fungi on the giant panda’s skin remains limited. In this study, samples from the giant panda skin in different seasons were collected, and the mycobiota were profiled by 18s rRNA gene sequencing. In total, 375 genera in 38 fungal phyla were detected, with Ascomycota, Basidiomycota, Streptophyta, and Chlorophyta as the predominant phyla and Trichosporon, Guehomyces, Davidiella, Chlorella, Asterotremella, and Klebsormidium as the predominant genera. The skin mycobiota of the giant panda changed in the seasons and the diversity and abundance of the skin fungi were significantly higher in spring, autumn, and summer than in the winter. Several dermatomycosis-associated fungi were detected as opportunists in the skin mycobiota of healthy giant pandas. Clinically dermatomycosis in giant panda is observed more in summer and autumn. In this study, the results indicated that the high diversity and abundance of the skin fungi may have enhanced the occurrence of dermatomycosis in autumn and summer and that dermatomycosis-associated fungi are the normal components of the skin mycobiota.